MARGIN PEMASARAN BUAH SALAK DI DESA PANGU DUA KECAMATAN RATAHAN TIMUR KABUPATEN MINAHASA TENGGARA - Regina ., Pangkey; Celcius ., Talumingan; Melissa Lady G. Tarore (Sam Ratulangi University, 2018)
This study aims to determine the pattern of marketing, calculate the amount of costs, margins and marketing benefits and farmer's share in Pangu Dua Village, which was held from June to August 2018. The dataused in this study are primary and secondary data. Primary data is data obtained by submitting a list of questions to farmers 10 respondents, collecting traders 5 respondents, retailers 3 respondents in Pangu Dua Village. While secondary data was obtained from Pangu Dua Village Office, and the internet. Data analysis in this study uses marketing channel analysis and marketing margin analysis. The results of the study show that there are four forms of marketing channels in Pangu Dua Village. Marketing channel I consists of farmers and consumers; marketing channel II consists of farmers, retailers, consumers; marketing channel III consists of farmers, collectors, supermarkets retailers and consumers; marketing channel IV consists of farmers, collectors and wholesalers between islands. Marketing channel III has the highest value, namely the cost of Rp. 345 per kilogram, margin of Rp. 11,000 per kilogram, and profit of Rp. 10,655 per kilogram. The highest portion received by farmers (farmer’s share) on marketing channel I is 100 percent. This research support the result of previous study by Kaparang's 2015 that the greater the marketing margin, the smaller the portion received by farmers, on the contrary the smaller the marketing margin the greater the portion received by farmers, can be accepted in this study.*jnkd+eprm*